Meta-analysis of negative-pressure wound therapy for closed surgical incisions. Issue 5 (16th March 2016) - Hyldig, N; Birke-Sorensen, H; Kruse, M; Vinter, C; Joergensen, J S; Sorensen, J A; Mogensen, O; Lamont, R F; Bille, C
Abstract: Background: Postoperative wound complications are common following surgical procedures. Negative-pressure wound therapy (NPWT) is well recognized for the management of open wounds and has been applied recently to closed surgical incisions. The evidence base to support this intervention is limited. The aim of this study was to assess whether NPWT reduces postoperative wound complications when applied to closed surgical incisions. Methods: This was a systematic review and meta-analysis of randomized clinical trials of NPWT compared with standard postoperative dressings on closed surgical incisions. Results: Ten studies met the inclusion criteria, reporting on 1311 incisions in 1089 patients. NPWT was associated with a significant reduction in wound infection (relative risk (RR) 0·54, 95 per cent c.i. 0·33 to 0·89) and seroma formation (RR 0·48, 0·27 to 0·84) compared with standard care. The reduction in wound dehiscence was not significant. The numbers needed to treat were three (seroma), 17 (dehiscence) and 25 (infection). Methodological heterogeneity across studies led to downgrading of the quality of evidence to moderate for infection and seroma, and low for dehiscence. Conclusion: Compared with standard postoperative dressings, NPWT significantly reduced the rate of wound infection and seroma when applied to closed surgical wounds. Heterogeneity between the included studies means that no general recommendations can be made yet. Abstract : Good for closed wounds too Video Abstract